Jesus as the Fulfillment of Salvation Symbolism: Theological Study of John's Gospel - Simamora, Ridwan Henry; Rotua, Dewi Magdalena; Nendissa, Julio Eleazer (Sekolah Tinggi Teologi Transformasi Indonesia, 2024)
Abstract: This study explores the continuity of the concept of salvation history (Old Testament) which is a topic of interest to readers of John's Gospel, having symbolic elements of Jewish festivals. Through a reading of John's Gospel, the reader discovers how not only Jesus is presented theologically as the Messiah but also the concrete fulfillment of what God revealed in the festivals and temples of that time. However, the understanding of how Jesus fulfills the symbols and festivals of the Old Testament has been the subject of theological debate. This research was conducted with a descriptive approach, by conducting a literature study related to salvation history from the perspective of the Gospel of John. It seeks to reveal how the Gospel of John reinterprets the festivals of salvation, offering a new understanding of Jesus as the true and final fulfillment of the new Passover for all believers and the establishment of Holy Communion in the Christian tradition. Jesus fulfills the symbolic meaning of the Feast of Salvation, and the Old Testament is seen as a shadow pointing to the ultimate reality in Christ. Jesus' participation in and reinterpretation of the feast is especially during His last supper, which is the Passover meal.